Implementation of the sommelier service and its role in the financial performance in the restaurant industry of Ukraine - Sokolenko, Anna; Krainyuk, Lyudmila; Semernina, Tetyana (Technology audit and production reserves, 2018)
The object of research is the introduction of sommelier services in restaurants of Ukraine. In practice, sommelier services in restaurants in Ukraine are rare in comparison with Western European countries. The problem lies in the lack of understanding of the positive impact of the introduction of sommelier services on the financial activities of restaurant establishments. There are also no studies on the identification of factors influencing the activities of sommeliers on restaurant income. Therefore, the work is aimed at identifying the reasons for the lack of sommelier services in restaurants in Ukraine, as well as at identifying prospects for sommeliers to work in restaurants. To solve the main research problems, such methods as system analysis, structuring, dialectical method, and control theory are used. With the help of these methods, the negative and positive consequences of sommelier services are identified and described. It is revealed that the sommelier performs duties that optimize the restaurant’s operations, contributes to the development of the restaurant business in general and saturates the wine market with new brands, and also increases customer satisfaction and restaurant income. The features of the "sommelier" concept are discussed, the varieties of the profession of sommelier are analyzed. It is determined what knowledge and skills a sommelier should have that will allow him to do the job efficiently. The sommelier function is considered in detail. The features of the sommelier in the restaurant are analyzed. The issue of obstacles to the introduction of sommelier services in restaurants in Ukraine is investigated. A number of advantages of introducing the services of sommeliers in restaurants are also identified. It has been proven that sommelier service is also considered as a cost ratio, and its use depends on the business concept and the expectations of the guests. Despite the positive aspects of introducing sommelier work in a restaurant, there are low arguments against using sommelier services. The research results can be used by researchers and experts working in the restaurant business. Consideration of the proposed approach will help ensure high efficiency of innovation in the restaurant industry of Ukraine.